Pengukuran Kualitas Pengalaman Pengguna pada Aplikasi Virtual Reality Untuk Properti Menggunakan UEQ - Setiabudi Sakaria; Subari; Mohd Zhafri Mohd Zhuki (ELANG: Journal of Interdisciplinary Research, 2026)
The use of Virtual Reality (VR) technology in the property industry has the potential to enhance the presentation of residential information in a more immersive way compared to conventional visual media. This study aims to evaluate the user experience of a VR property application. The research method used was quantitative with a survey approach. The primary instrument was the User Experience Questionnaire (UEQ), which includes six scales: attractiveness, perspicacity, efficiency, dependability, stimulation, and novelty. The results showed that Pragmatic Quality, with a mean score of 1.1328125, according to the benchmark, was classified as below average. Hedonic Quality, with a mean score of 1.375, was classified as good. Overall, the mean score of 1.25 was classified as above average. The Virtual Reality application for property provides an excellent user experience, particularly in terms of attractiveness, stimulation, and novelty, and has a competitive UX quality compared to other digital products.